BUSINESS MAINTENANCE AND ENSURING ITS DEVELOPMENT STABILITY ON THE BASIS OF QUALITY MANAGEMENT - N. Stavitskaya (Управленческие науки)
The topic actuality is determined by the importance of solving the problem to maintain business and ensure its development stability especially under crisis conditions and also by ambiguous attitude towards peculiarities and possibilities to use international standards and quality management tools for reaching ongoing success. Some aspects of this direction from the point of view of quality management are considered in this article. The role of quality management in ensuring business competitiveness, main tools and the problems of their usage in order to maintain and further develop it are analyzed. The necessity to choose the tools relevant to concrete situations and forecasting the possible ramification defining business performance and efficiency is noted. A special role is given to technological factors and diversification. The suggested recommendations will allow the CEO to emphasize the most essential factors defining the further business future and make a decision relevant to concrete conditions.